Evaluating candidate wetlands for the assisted colonization of the western swamp turtle Pseudemydura umbrina in a changing climate: Macro‐invertebrate food resources and turtle diet. Issue 7 (6th April 2021) - Schmölz, Katja; Pinder, Adrian; Kuchling, Gerald; Gollmann, Günter
Abstract: The natural habitat of the western swamp turtle ( Pseudemydura umbrina Siebenrock, 1901) – the ephemeral, winter wet swamps north of Perth, Australia – is in danger owing to climate change and habitat fragmentation. The decline in rainfall in this area over the last five decades is predicted to continue, shortening the annual activity period for the turtles and potentially shifting their optimal climate zone to the south. Assisted colonization to wetlands in the cooler far south west of the state is one management response. As a contribution to such a measure, the diversity and abundance of food resources and consumption by turtles were evaluated at two potential and one existing colonization site. Thirty‐five captive‐bred juvenile P. umbrina were temporarily released into three sites: Moore River Nature Reserve north of Perth (into which the species had already been successfully translocated) and Meerup and East Augusta in the cooler far south of Western Australia. Food resources were assessed using sweep nets to sample invertebrates on two occasions at each wetland. Separate samples were collected for biomass determination and for assessing invertebrate diversity. Feeding by turtles was assessed by stomach flushing. Neither biomass nor biodiversity differed significantly between the southern sites and the reference site north of Perth. Stomach contents varied greatly, from 0 to 62 animals per turtle. The main prey items were beetles, ostracods, isopods and tadpoles. Each candidate wetland provided adequate food resources, indicating that assisted colonization to the cooler south coast of Western Australia has the potential to become a reasonable conservation tool to ensure the long‐term survival of P. umbrina .